The study of the impact of 4,4'-methylenbis (2-methoxyaniline) on adhesive properties of the epoxy matrix for protective coatings of transport means - V. M. Yatsyuk, R. Yu. Negrutsa, A. V. Buketov, О. М. Bezbakh (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
It is shown that one of the main means of regulating the structure and properties of polymer composites is their physical modification. It has been proven that the introduction of plasticizers and fillers into the binder makes it possible to improve the properties of materials. The effect of the 4,4'-methylenebis (2-methoxyaniline) modifier on the adhesion properties of the epoxy matrix has been investigated. The optimal concentration of the modifier has been established, ensuring maximum indicators of the adhesive strength of the matrix when separated from the steel St. 3 base. The method of IR-spectroscopy established the chemical structure of the modifier, confirming its activity to interact with the epoxy oligomer in the course of polymerization with a binder. This provides obtaining material not only with improved adhesion strength, but also with negligible residual stresses.